Efektivitas Peningkatan Pendapatan Nelayan Kepiting Rajungan (Portunus pelagicus) melalui Pendekatan Analisis Biaya di Kabupaten Situbondo: Effectiveness of Increasing Income of Crab Fishermen (Portunus pelagicus) Through Cost Analysis Approach in Situbondo District - Laily, Dona Wahyuning; Roidah, Ida Syamsu; Rizkiyah, Noor (Jurnal Ilmiah Manajemen Agribisnis, 2024)
The purpose of this study was to obtain further information about the income of fishermen from fishing activities, processing in Small Industries and the value of the marketing industry margin using surveys, interviews and observation methods. Sampling was carried out using cluster sampling. The types of data collected were primary and secondary data. Data were analyzed using qualitative and quantitative approaches. The results showed that the income of blue crab fishermen from fishing activities alone could reach Rp. 644,660 per month with an R / C Ratio of 2.35 average value. From the processing of crabs to become crab meat in Small Industries, add product value accompanied by quality and in accordance with SOP, SSOP and labor absorption. Marketing institutions involved in line I (Collector Fisherman) obtain a margin of Rp. 2,000, (processing) obtained a margin of Rp. 5,250 and for marketing line 2 (processing) obtained a margin of Rp. 7,250.